The relationship between social media marketing and academic library service quality / Siti Nurul Atikah Alang Achik and Mohd Razilan Abdul Kadir - Alang Achik, Siti Nurul Atikah; Abdul Kadir, Mohd Razilan (Faculty of Information Management, 2022)
This paper presents the study on the relationship between social media marketing and service quality of international private college libraries in Selangor. The study hypothesized three dimensions that posited to influence the service quality of the college's library namely perceived usefulness, perceived ease of use and technology features. The quantitative research method via survey is opted where questionnaires were distributed to a total of 252 respondents. Findings indicated that the majority of the respondents were coming from non-technical programs and exists a significant and high positive correlation between service quality and the posited three service quality dimensions: perceived usefulness (r=0.731, p=0.000), perceived ease of use (r=0.766, p=0.000) and technology features (r=0.795, p=0.000). Findings indicated that academic library social media marketing activities may help students more to fulfil their study needs however it also found that they also face challenges, less anticipation through social media and did not receive a response (to get help) through library social media platforms as quickly as they expect. The study suggests that the library management should be aware of the current students' needs/issues/behaviour towards the trend of using social media technology as to ensure the service quality of the academic library meets their expectations